Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Keywords: dept.nur